Evidence-inspired Urban Livability: Leveraging Indigenous and Vernacular Housing Practices for Total Sustainability - Afzal, Sara; Faruquie, Daud Salim; Afzal, Maham (Calibrating Urban Livability in the Global South, 2024)
Conventional construction methods pose a significant threat to our overall sustainability. This has prompted a re-evaluation of the time-tested, sustainable techniques found in vernacular and indigenous building practices around the world. Sustainable housing, according to our criteria, embodies a holistic sustainability approach that encompasses four key facets: environmental, economic, social, and cultural, often referred to as the four pillars of sustainability. Acknowledging the inherent link between sustainability and livability, this study is premised on the idea of assimilating comprehensive sustainability practices from indigenous and vernacular traditions worldwide. Methodology: The objective of this evidence-based scoping review is to examine the impact of indigenous and vernacular architectures on urban livability through gaining inspiration from their total sustainability. A comprehensive search strategy aligned with the PRISMA statement was devised. Primary concepts and synonyms were identified for inclusivity. Boolean operators were used to combine keywords effectively. Subject headings were considered for relevant databases. Filters and limits were applied as necessary. Grey literature and manual searches were conducted for comprehensiveness. Inclusion criteria included peer-reviewed publications, conference proceedings, government reports, theses, and dissertations from January 2000 to present. The focus was on English language publications addressing sustainability features in vernacular and indigenous housing globally. Aspects like energy efficiency, local material utilization, cultural significance, adaptability, and resilience were considered. Grey literature, non-English publications, studies before January 2000, and region-specific studies were excluded. In data extraction and analysis duplicates were removed, initial screening by researchers DSF and SA was conducted based on titles and abstracts, MA organized data in MS Excel sheets, full-text manuscripts were obtained and evaluated for eligibility, extracted data was catalogued in a Microsoft Excel spreadsheet. The search based on the inclusion criteria yielded a total of 523 articles of which 26 were retained for final analysis and reviewing. The collection of selected studies, specifically examining their alignment with the principles of total sustainability, serves as a comprehensive exploration of diverse practices and ideas. In addition, the review discerns key technical and practical details related to the intricacies of contemporary urban life. Results: The indigenous methods identified demonstrated common sustainability traits, including adaptability to local climates, thermal comfort optimization, meticulous building orientation and design, use of indigenous materials and techniques, preservation of cultural identity, respect for vernacular heritage, promotion of social self-sufficiency, enhancement of visual connectivity, and the fostering of family and community gatherings. These practices epitomize key aspects of sustainability, such as recyclability, reusability, and renewability. The review identified key technical and practical details related to the intricacies of contemporary urban living, emphasizing the importance of understanding local context. The study explores the multifaceted nature of social sustainability in the context of indigenous and traditional architectures, providing valuable insights for promoting cohesive, culturally rich, and socially sustainable urban environments. Specifically, the study proposes a resilience framework and participatory approach for designing sustainable and resilient post-disaster housing solutions, highlighting the interlinkages between Sustainable Development Goals (SDGs) related to health and water. Review further examined the four aspects of total sustainability and highlighted the importance of natural ventilation, solar shading, and passive methods for climate control, recycling, energy efficiency, and use of locally available materials, contributing to a healthy urban environment. Additionally, studies have highlighted the importance of indigenous materials in building envelopes for thermal comfort and affordable housing, emphasizing local resources, for energy efficiency in urban settings. While highlighting its potential contribution to sustainable urban life, the review emphasizes the importance of climate-conscious designs, community engagement, and resource-efficient building methods. Vernacular Housing in Vietnam, Indigenous African Building Techniques, Passive Control Methods of Kerala Traditional Architecture, Traditional Buildings in Haiti, Vernacular Buildings in Portugal, Integration with Nature in Tribal Habitats, Sustainability and Cultural Growth in Madeira Island, Learning from Traditional Construction in Spain, and Sustainable Housing Design in Mardin, Turkey all emphasize the importance of climate-conscious designs, community engagement, and resource-efficient building methods. Policy Projection: Incorporating evidence-based policy recommendations bolsters the legitimacy of sustainability concepts and theories by anchoring them in tested and documented methodologies and outcomes. Although our study's recommendations are both precise and effective, their applicability can vary with geographical contexts, particularly concerning environmental sustainability. For the other three dimensions, our recommendations shift their focus towards aspects of daily life, including neighborhood social capital, family relationships, citizenship, trust in interpersonal connections, social inclusion, well-being, habitability, and family and community dynamics. The study advocates for collaboration between architects and engineers to develop reconstruction strategies based on local methods and resources, showcasing the significance of indigenous knowledge in building resilience. Moreover, the study suggests that these strategies can be applied in contemporary urban design to create environmentally friendly and comfortable living spaces. This comprehensive model underscores a synergistic relationship between evidence and practice, with the overarching goal of enhancing ecological health and indoor air quality within the built environment.